1992
DOI: 10.1073/pnas.89.17.8125
|View full text |Cite
|
Sign up to set email alerts
|

Mutants of complement component C3 cleaved by the C4-specific C1-s protease.

Abstract: To identify some of the structural features determining specific protease recognition of complement components C3 and C4, we used site-specific mutagenesis to construct mutants of murine C3 that are cleaved by the C4-specific Cis protease. Insertion of three amino acid residues corresponding to residues at the Cis cleavage site of human C4 into murine C3 at the analogous C3 convertase cleavage site was adequate to render the mutant protein susceptible to Cis cleavage. In addition, insertion of C3-specific resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…Collectively, these data suggest that the mutations have not introduced conformational alterations that extend beyond the target segment. The partial defect observed on cleavability by the classical pathway C3 convertase in virtually all of the mutants is in keeping with a previous study (50) showing that susceptibility of mouse C3 to cleavage by the alternative pathway C3 convertase was quite sensitive to sequence alterations in the segment immediately downstream of the cleavage site.…”
Section: General Characterization and Conformational Integrity Of Thesupporting
confidence: 72%
“…Collectively, these data suggest that the mutations have not introduced conformational alterations that extend beyond the target segment. The partial defect observed on cleavability by the classical pathway C3 convertase in virtually all of the mutants is in keeping with a previous study (50) showing that susceptibility of mouse C3 to cleavage by the alternative pathway C3 convertase was quite sensitive to sequence alterations in the segment immediately downstream of the cleavage site.…”
Section: General Characterization and Conformational Integrity Of Thesupporting
confidence: 72%
“…In previous work we suggested that recognition of C3 and C5 by their respective convertases requires interactions at sites distal to the activation cleavage sites in these proteins (4,5). To find these putative distal sites, we developed a strategy focused on indels in the C345 protein family.…”
Section: Discussionmentioning
confidence: 99%
“…However, in previous work, we found that the susceptibility of C4 to C1s activation can be almost completely eliminated by deletion of three residues near the activation site (3) and, conversely, that C3 and C5 can both be rendered susceptible to C1s by substituting C4-like sequences near their activation sites (4,5). These results indicated that recognition by C1s primarily involves interactions with residues flanking the cleavage site.…”
mentioning
confidence: 99%
“…In summary, the molecular analysis of the trk mutant alleles supports the functional importance of the domains found the pre- (Fritzinger et al 1992) (m) mouse (Wetsel et al 1984); (r) rat (Misumi et al 1990); and (h) human (De Brujin et al 1985)l. Cleavage of C3 to generate C3a and C3b (arrow) appears to depend on three distinct sub-domains designated A, B, and S. It has been proposed that region A contains the cleavage site, region B constitutes a binding site for the protease, and region S functions as a spacer, the length and acidity of which appear important for the normal cleavage event to occur (Mathias et al 1992). All three of these subdomains appear to be conserved in the trk protein.…”
Section: A a T T T T G C T G C A C G T G A C T T C C G G A A T T T G mentioning
confidence: 99%